ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS KEMISKINAN RUMAHTANGGA DI KOTA PARIAMAN - Haris Mendra; Syamsul Amar (Program Studi Magister Manajemen, 2016)
The purpose of this research are to analysis the influence of education of household head, working status of household head, and family size in Pariaman city. This analysis use Logistic Regression Model to show the probabilities of poverty with Wald Test analysis to know influence of independent variabel partially effect on dependent variabel, Chi-Square analysis to know the influence of independent variabel simultaneously effect on dependent variabel. Then use Odd Ratio analysis to know the probabilities of poverty. The result of this study found that the influence of education of household head to poverty is negative and significant, this mean is the more higher of education of household head will effect the more lower of poverty. The influence of working status of household head to poverty is negative and significant too, this mean is more formal the working status of household head will effect more lower of poverty. Then, the influence of family size to poverty is negative and significant too, the meaning is more small of the number of the family will effect more lower of poverty. Cause of education of household head, working status of household head and fa,ily size effecly more andt significant to poverty in Pariaman city, so that the Government should more priority the policies that can increase the capabilities of the peoples in the city to the three variabel, example with give more practice to increase the capability, education to setting the maternity and many more. Keywords : Poverty, education of household head, working status of household Head, and family size.